Determination of genetic stability of Agapanthus praecox ssp. minimus grown in vitro via cytological analysis - Yaacob, J.S.; Mat Taha, R.; Mohajer, S. (2014)
Ploidy analysis revealed percentage of polyploid cells in vitro increased concomitantly with culture time, indicative of genetic instability under in vitro conditions. Chromosome number was stable (2n=2x=30) throughout culture period, indicating no occurrence of early somaclonal variation.